Developing a Competency Framework for Population Health Graduate Students Through Student and Faculty Collaboration. (September 2021) - Miller, Laura; Brushett, Sara; Ayn, Caitlyn; Furlotte, Kirk; Jackson, Lois; MacQuarrie, Madison; Massie, Ariane S.; Mathias, Holly; McKay, Madeleine; Meisner, Brad A.; Moritz, Lauren; Stilwell, Christie; et al.
Defining competencies within health disciplines is important because it provides a shared understanding of the fundamental knowledge, skills, and attitudes necessary for research and practice while also offering a practical reference point for academic preparation and professional development. However, existing literature regarding competency frameworks does not address the unique needs of interdisciplinary population health research graduate students. The purpose of this project was to understand the competencies desired by interdisciplinary population health research graduate students within the Healthy Populations Institute (HPI) at Dalhousie University and to create a competency framework on which training and program development could be based. A student-led initiative was undertaken to identify core competencies necessary for interdisciplinary population health research graduate students from both traditional (e.g., health promotion) and nontraditional health (e.g., political science) backgrounds. Data were collected and analyzed via three phases: environmental scan, community resource mapping, and consultations with HPI research scholars. Through the environmental scan, core competencies and guiding principles were identified. Community resource mapping of local employment, volunteer, educational, and/or skill-building opportunities resulted in the development of a database. Consultations confirmed the validity of competencies identified in the scan and elicited further resources and suggestions for educational and professional skill development. This project resulted in a unique competency framework that will inform ongoing program development and foster additional opportunities for graduate students within HPI. The process of creating this framework may also be of value to other universities wishing to develop or refine their own set of competencies.